A New Design Approach for a Compact Microstrip Diplexer with Good Passband Characteristics - Rezaei, Abbas; Yahya, Salah I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
This paper presents an efficient theoretical design approach of a very compact microstrip diplexer for modern wireless communication system applications. The proposed basic resonator is made of coupled lines, simple transmission line and a shunt stub. The coupled lines and transmission line make a U-shape resonator while the shunt stub is loaded inside the U-shape cell to save the size significantly, where the overall size of the presented diplexer is only 0.008 λg2 . The configuration of this resonator is analyzed to increase intuitive understanding of the structure and easier optimization. The first and second resonance frequencies are f o1 = 895 MHz and f o2 = 2.2 GHz. Both channels have good properties so that the best simulated insertion loss at the first channel (0.075 dB) and the best simulated common port return losses at both channels (40.3 dB and 31.77 dB) are achieved. The presented diplexer can suppress the harmonics acceptably up to 3 GHz (3.3 fo1 ). Another feature is having 31% fractional bandwidth at the first channel.